miR-30a acts as a tumor suppressor by double-targeting COX-2 and BCL9 in H. pylori gastric cancer models - Xuan Liu (Nature Portfolio, 2017)
Abstract Helicobacter pylori (H. pylori) is one of the most important factors that affect the development of gastric cancer, and its mechanism remains un-elucidated. Our present study found that, miR-30a is crucial for regulating the growth and migration of H. pylori infected gastric cancer in vitro by targeting COX-2 and BCL9. In details, double-stranded miR-30a precursor produced two single-stranded and matured miRNAs including miR-30a-3p and miR-30a-5p, which played significant biological functions in two different manners. First, miR-30a-3p inhibited COX-2 expression and regulated nuclear translocation of β-catenin, and second, miR-30a-5p targeted BCL9 to regulate TCF/LEF promoter activity followed by affecting β-catenin downstream target gene expression. In vivo, miR-30a knockout mice were successfully achieved using CRISPR/Cas9 gene editing technology. Compared with H. pylori-infected wild-type mice, H. pylori-infected miR-30a knockout mice showed increased incidence of chronic gastritis, chronic atrophic gastritis, atypical hyperplasia, and other precancerous lesions or adenocarcinoma manifestations in the antral or gastric mucosa of mice, as well as regulation of genes closely associated with tumor development. Taken together, miR-30a acts as a tumor suppressor by double-targeting COX-2 and BCL9, and significantly affects the development of H. pylori-induced gastric cancer, shedding new light on the mechanisms underlying H. pylori-associated gastric cancer.